The future of building information modeling: An exploratory study - Chua, Xin Jie (2023)
Building Information Modelling (BIM) has been widely adopted in the construction sector across various countries, including Malaysia, over the last decade. It is time to review how the industry has made use of BIM and explore its future. This research aims to explore the future of BIM adoption in the Malaysian construction industry by reviewing the changing narratives of BIM, exploring the current adoption of BIM in Malaysian construction industry, and anticipating its future adoption. The literature review identified 13 ways of BIM adoptions and 11 possibilities for the future of BIM. An online questionnaire survey was used to gather empirical data from industrial practitioners, and 206 valid responses were received. The questionnaire's internal consistency was assessed using Cronbach's alpha reliability analysis, and the randomness of the result was tested using the Chi-Square Test. The Kruskal Wallis H-test was used to determine significant differences in current practices and future BIM adoption according to companies' business activities, profession, and working experience. The results showed that authoring is the most common use of BIM in Malaysia, and BIM is viewed as an integral part of the construction sector's future. Architects are the most proactive in adopting BIM, while quantity surveyors perceive its importance to be higher than other professionals. The research findings can help the construction industry in creating, a strategic plan for the future BIM adoption. Regulatory bodies can implement necessary improvements to expedite the industry's maturity in BIM adoption and support academic advancements in research, innovation, and curriculum creation.